Teachers’ and Students’ Perceptions of the Benefits of Muhadhoroh Activities for English Public Speaking at the Islamic Boarding School Babul Hikmah - Manasikana, Arina; Kadaryanto, Budi; Shafwati, Dian (English Language Education Study Program, 2025)
This study explores teachers’ and students’ perceptions of Muhadhoroh activities in enhancing English public speaking skills at the Islamic Boarding School Babul Hikmah. Muhadhoroh, a structured public speaking practice held regularly in pesantren environments, helps build confidence, fluency, and articulation. This qualitative research employed semi-structured interviews with five teachers and five students and was analyzed thematically using NVivo. Findings revealed that Muhadhoroh supports linguistic development, especially in pronunciation, vocabulary, and confidence. Nervousness and grammatical challenges were commonly noted. Teachers emphasized structure and accuracy, while students favored emotional comfort and small-group training. The